1998
DOI: 10.1152/ajpcell.1998.274.1.c112
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates oxygen uptake and hydrogen peroxide release by the isolated beating rat heart

Abstract: Isolated rat heart perfused with 1.5–7.5 μM NO solutions or bradykinin, which activates endothelial NO synthase, showed a dose-dependent decrease in myocardial O2uptake from 3.2 ± 0.3 to 1.6 ± 0.1 (7.5 μM NO, n = 18, P < 0.05) and to 1.2 ± 0.1 μM O2 ⋅ min−1 ⋅ g tissue−1 (10 μM bradykinin, n = 10, P < 0.05). Perfused NO concentrations correlated with an induced release of hydrogen peroxide (H2O2) in the effluent ( r = 0.99, P < 0.01). NO markedly decreased the O2 uptake of isolated rat heart mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 27 publications
4
116
0
Order By: Relevance
“…The mitochondrial electron transport chain produces O 2 ·-from two sites, the co-enzyme Q region and NADH dehydrogenase (Boveris 1977;Poderoso et al 1998a). Several studies have suggested a role for mitochondrial production of O 2 ·-in stimulation of vascular cell apoptosis Cadenas et al 2000;Panaretakis et al 2001).…”
Section: Mitochondrial Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial electron transport chain produces O 2 ·-from two sites, the co-enzyme Q region and NADH dehydrogenase (Boveris 1977;Poderoso et al 1998a). Several studies have suggested a role for mitochondrial production of O 2 ·-in stimulation of vascular cell apoptosis Cadenas et al 2000;Panaretakis et al 2001).…”
Section: Mitochondrial Respirationmentioning
confidence: 99%
“…H 2 O 2 is a byproduct of mitochondrial processes (Poderoso et al 1998a) and superoxide dismutase (Griendling et al 2000a;Salvemini et al 2002). In previous studies, we found that higher than physiologic concentrations of H 2 O 2 result in higher intracellular superoxide (O 2 .-) in endothelial cells (Coyle et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1). The reversible NO inhibition of cytochrome oxidase occurs at nanomolar levels of NO (11)(12)(13), so that NO is potentially a physiological regulator of respiration (3,(14)(15)(16)(17). NO inhibits by reacting with either the reduced or oxidised binuclear (oxygen-binding ) site of cytochrome oxidase to give either cytochrome a 3 2C -NO or cytochrome a 3 3C -NO 2 ¡ (18)(19)(20).…”
Section: No Actions On Mitochondriamentioning
confidence: 99%
“…In addition to stimulating H 2 O 2 production, NO or RNS can also inhibit catalase, deplete cellular glutathione and inhibit glutathione peroxidase, thus increasing H 2 O 2 levels in cells (1,16,34). Indeed, NO and H 2 O 2 have been found to be synergistic in killing cells, possibly in part by superoxide dismutase-catalysed peroxynitrite production (35).…”
Section: No Actions On Mitochondriamentioning
confidence: 99%
“…These reactions are regulated by the matrix concentration of nitric oxide (NO), which diffuses to the mitochondria from the cytosolic NO synthase (NOS) isoforms and is thought to be produced also locally by a mitochondrial NOS variant (11). In rat heart, skeletal muscle and liver mitochondria (15,57,58), isolated rat hearts (59), and whole animals (68), NO at physiological concentrations binds reversibly and in competition with oxygen (O 2 ) to the reduced binuclear center Cu B /a 3 of cytochrome-c oxidase (complex IV) of the electron transport chain (ETC) and inhibits mitochondrial O 2 uptake. At slightly higher concentrations, NO oxidizes ubiquinol of ubiquinolcytochrome c reductase (complex III) to increase unstable ubisemiquinone, which, by univalent electron transfer to O 2 , produces the reactive O 2 species (ROS) superoxide (O 2 ⅐ Ϫ ) (57,58).…”
mentioning
confidence: 99%